Formalization of the General Model of the Green Economy at the Regional Level - Potravny, Ivan Mikhaylovich; Novoselov, Andrey Leonidovich; Gengut, Igor Borisovich (Economy of Regions, 2016)
The subject-matter of the article is the research of the problems of economic and mathematical modelling of the green economy at the regional level. The purpose of the research is the substantiation and development of economic and mathematical tools for the modelling of economic and ecological systems at the regional level on the basis of the principles of the green economy. The hypothesis of the study is based on the thesis that in the conditions of the resource exhaustion and depletion of natural capital, the technogenic deposits as well as production waste and consumption can be considered as the resource base for modern production, whose use leads to the elimination of accumulated environmental damage and substitution of natural resources. In the article, the approaches to the system modelling problems are considered to develop the green economy at the level of the country and its regions. The relevance of the transition to a green economy is confirmed by the theoretical and practical research in the field of the cyclic development of socio-eco-economic systems. A number of formalized models and methods for solving current environmental-economic issues including the economic valuation of accumulated environmental damage, eco-economic assessment of the efficiency of natural resource substitution with resource-substitute are proposed as well as the choice of an optimal set of resources-substitutes taking into account the financial and natural resource constraints. The standard models of green growth are considered. These models take into account the exhaustion of natural resources, involvement of the resources of technogenic deposits in the economic circulation through the implementation of investment projects on the elimination of accumulated environmental damage. The results of the study may be used in the different regions of the country for the justification and implementation of investment projects in the framework of the Federal Target Program “Elimination of accumulated environmental damage” for 2015-2026.